2019
DOI: 10.1186/s13063-019-3196-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photobiomodulation on the severity of oral mucositis and molecular changes in head and neck cancer patients undergoing radiotherapy: a study protocol for a cost-effectiveness randomized clinical trial

Abstract: BackgroundOral mucositis (OM) is the most frequent and debilitating acute side effect associated with head and neck cancer (HNC) treatment. When present, severe OM negatively impacts the quality of life of patients undergoing HNC treatment. Photobiomodulation is a well-consolidated and effective therapy for the treatment and prevention of severe OM, and is associated with a cost reduction of the cancer treatment. Although an increase in the quality of life and a reduction in the severity of OM are well describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
0
23
0
4
Order By: Relevance
“…The PBM protocol recommended to prevent OM is the use of a low-power laser with a wavelength of 660nm, energy density of 6.2J, in 72 application points, 10 seconds per point, during 03 days a week, alternately [11]. Other studies [38][39][40][41][42] presented different PBM protocols, which ranged in energy density from 1J to 6J, with application points from 09 to 58 points, alternating to continuous and different conductive media. Previous data from our group [43], whose PBM protocol included low-power AsGaAl laser, 660nm, 86.7 mW, energy density of 2J, applied to 28 points in the oral cavity for 3 seconds at each point, was also unable to prevent the emergence of OM.…”
Section: Gonçalves Et Al (2018)mentioning
confidence: 99%
“…The PBM protocol recommended to prevent OM is the use of a low-power laser with a wavelength of 660nm, energy density of 6.2J, in 72 application points, 10 seconds per point, during 03 days a week, alternately [11]. Other studies [38][39][40][41][42] presented different PBM protocols, which ranged in energy density from 1J to 6J, with application points from 09 to 58 points, alternating to continuous and different conductive media. Previous data from our group [43], whose PBM protocol included low-power AsGaAl laser, 660nm, 86.7 mW, energy density of 2J, applied to 28 points in the oral cavity for 3 seconds at each point, was also unable to prevent the emergence of OM.…”
Section: Gonçalves Et Al (2018)mentioning
confidence: 99%
“…Although in our case the laser was applied only for advanced lesions, studies also show the possibility of preventive use of the laser before and during CT and RT conducted on the entire mucous membrane, which significantly reduces the risk of advanced OM and reduces its duration [ 23 , 24 , 25 ]. Martins et al analyzed the cost-effectiveness of OM treatment of a cycle of PBM treatments compared to pharmacological therapy based on a mouthwash with 0.12% chlorhexidine and oral ointment with hydrocortisone 5 mg, neomycin 5 mg, troxerutin 20 mg, ascorbic acid 0.5 mg, and benzocaine 2 mg. PBM therapy is not only a more effective treatment, but is also advantageous in terms of costs which are much lower for a single oncological patient and the entire health care system [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for this research has been previously reported [39]. This study was registered in the Brazilian Registry of Clinical Trials (REBEC—RBR‐5h4y4n) and was approved by the Ethics Research Committee of Universidade Federal de Goiás (Protocol 2.053.687/2017) and Araujo Jorge Cancer Hospital (Protocol 2.131.323/2017).…”
Section: Methodsmentioning
confidence: 99%